Identifying high-risk adult AML patients: epigenetic and genetic risk factors and their implications for therapy. Issue 4 (2nd April 2016) - Bret, Caroline; Viziteu, Elena; Kassambara, Alboukadel; Moreaux, Jerome
ABSTRACT: Acute myeloid leukemia (AML) is a heterogeneous disease at molecular level, in response to therapy and prognosis. The molecular landscape of AML is evolving with new technologies revealing complex panorama of genetic abnormalities where genomic instability and aberrations of epigenetic regulators play a key role in pathogenesis. The characterization of AML diversity has led to development of new personalized therapeutic strategies to improve outcome of the patients.